Effects of chronic irisin treatment on brain monoamine levels in the hypothalamic and subcortical nuclei of adult male and female rats: An HPLC-ECD study - Yardimci, Ahmet; Ertugrul, Nazife Ulker; Ozgen, Aslisah; Ozbeg, Gulendam; Ozdede, Mehmet Ridvan; Ercan, Eda Coban; Canpolat, Sinan (Elsevier Ireland Ltd, 2023)
Monoaminergic systems are known to be involved in the pathophysiology of neuropsychiatric disorders and vegetative functions due to their established influence on hypothalamic and subcortical areas. These systems can be modulated by lifestyle factors, especially exercise, which is known to produce several beneficial effects on reproduction, brain health, and mental disorders. The fact that exercise is sensed by the brain shows that muscle-stimulated secretion of myokines allows direct crosstalk between the muscles and the brain. One of such exercise-induced beneficial effects on the brain is exhibited by irisin-a recently discovered PGC-1 alpha-dependent adipo-myokine mainly secreted from skeletal muscle during exercise. Thus, we hypothesized that irisin may affect central monoamine levels and thus play an important role in the muscle-brain endocrine loop. To test this assertion, for 10 weeks, vehicle (deionized water) or 100 ng/kg irisin was injected intraperitoneally once a day to 12 male and 12 female rats after which the levels of monoamines and their metabolites were determined by HPLC-ECD. In the hypothalamic nuclei, irisin significantly decreased dopamine (DA) metabolite 3,4-dihydroxy-phenylacetic acid (DOPAC) (p < 0.05), DOPAC/DA ratio (p < 0.01) and noradrenaline (NA, p < 0.05) levels in the anteroventral periventricular nucleus (AVPV), and DOPAC and NA levels in the medial preoptic area (mPOA) (p < 0.05), having a crucial role in reproduction and sexual motivation, respectively. On the other hand, irisin significantly increased DOPAC levels in the lateral hypothalamic area (LHA) (p < 0.05), which acts as a hunger center, while it significantly decreased the levels of DA, NA, and its metabolite 3,4-dihydroxyphenylglycol (DHPG) in the ventromedial hypothalamic nucleus (VMH) as a known satiety center (p < 0.05). In nucleus accumbens (NaC), irisin significantly reduced 5-hydroxyindoleacetic acid (5-HIAA) levels (p < 0.05), which are implicated in autism spectrum disorder (ASD) physiopathology. It also significantly increased DA levels in this area, thus exhibiting positive effects on depression and sexual dysfunction in men. On the other hand, it significantly decreased serotonin (5-HT) (p < 0.01) and its metabolite 5-HIAA levels in the medial amygdala (MeA) (p < 0.05), indicating that it may play a role in social behaviors. Moreover, it significantly attenuated NA levels in the same subcortical area (p < 0.01), which is directly involved in stress-induced activation of the central noradrenergic system. These findings demonstrate for the first time that irisin induces significant changes in monoamine levels in many hypothalamic nuclei involved in feeding behavior and vegetative functions, as well as in subcortical nuclei related to neuropsychiatric disorders.
Keywords: Exercise; Irisin; Monoamines; HPLC-ECD; Hypothalamic nuclei; Subcortical nuclei